On the Introduction of the Use of Ceramic Tiles in Old Rus Architecture - Matveev, Vasilii N. (Actual Problems of Theory and History of Art, 2024)
The earliest known example of ceramic tiles appeared in Old’ Rus architecture is found in the Church of the Tithes, where they were a direct copy of the opus sectile laying technique. Since the 11th century, in the repair layers of the Church of the Tithes and the in the choirs of St. Sophia Cathedral, tiles with an abstract marble pattern have been introduced. Towards the end of the 11th century a large number of square tiles with monochrome glaze have emerged. In general, the tile layouts in Old Rus were a provincial version of the Byzantine opus sectile. The tradition of using ceramic tiles could not have been transferred from Constantinople, where floor ceramics were not used at all, or Bulgaria, where floor tiles were used in combination with marble and where all building activity ceased in the first third of the 10th century. A more likely place of initial borrowing was Crimea, where construction activity was not interrupted until the advent of Old Rus architecture. This region boasts a monument, Partenit Basilica, with the laying technique which would become the leading one in Old Rus during the 10th–12th centuries. It is therefore plausible that it was the masters of Crimean origin, who were the ones who brought the tradition of using tiles in floors to Old Rus. An additional argument for this hypothesis is the Crimean origin of Anastas Korsunyanin, who was the first dean, and, possibly, the construction manager of the Church of the Tithes.
Keywords: ceramic tiles; Tithe church; mosaics opus sectile; Great Preslav; Parte